Analisis Indeks Kekeringan Meteorologis Lahan Gambut Di Pulau Tebing Tinggi Provinsi Riau Menggunakan Data Satelit Tropical Rainfall Measuring Mission (TRMM) - Syuhaya Wanisakdiah; Sigit Sutikno; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Drought is one of the phenomena that often happen every year in some regions of Indonesia. Therefore, it is necessary to do drought index analysis to know the level of drought so that it can be used for early against peat fire disaster. Analyzing level of drought in peat land in this research used SPI (Standardized Precipitation Index) method based on GIS (Geographic Information System). The data used were monthly rainfall data taken from TRMM (Tropical Rainfall Measuring Mission) satellite in the area of Tebing Tinggi Island from 2009 -2016. The calculation of SPI index was conducted on monthly and half monthly period in each designed grid. The results show that in monthly period, the severe drought index values occurred on grid 21, February of 2014 at -4.007 (Very Dry), whereas the period of half monthly values of severe drought index occurred on grid 4, the month of February 2 of 2014 was -4.896 ( Very Dry). The results indicated that the calculation of the half monthly period is better than the monthly period, because the result of the half monthly period is more detailed. Keywords: Drought Index, Standardized Precipitation Index, TRMM, Drought Distribution Mapping.